Sound Field Reproduction - Rabenstein, Rudolf; Spors, Sascha (Springer Handbook of Speech Processing, 2008)
Multichannel sound field reproduction aims at the physically correct synthesis of acoustical wave fields with a large number of loudspeakers. It goes beyond stereophony by extending or eliminating the so-called sweet spot. This chapter presents the physical and mathematical description of various methods for this purpose and presents the physical and mathematical background of several methods for multichannel sound field reproduction. ©Spring